Involving people with type 2 diabetes in facilitating participation in a cardiovascular screening programme - Marie Dahl; Susanne Friis Søndergaard; Axel Diederichsen; Jens Søndergaard; Trine Thilsing; Jes S. Lindholt (Wiley, 2021)
Abstract Background Knowledge is lacking about how to increase uptake among people with type 2 diabetes (T2D) invited to preventive initiatives like cardiovascular screening. Aim To explore how to improve participation of people with T2D in cardiovascular screening using patient and public involvement (PPI). Methods Patient and public involvement was included in a qualitative research design. From April to October 2019, we invited 40‐ to 60‐year‐old people with T2D (n = 17) to individual consultative meetings, using an interviewing approach. Before the interviews, participants were asked to read a proposed invitation letter to be used in a cardiovascular screening programme. Inductive content analysis was undertaken. Results Participants considered cardiovascular screening important and beneficial from both a personal and social perspective. We found that the relational interaction between the person with T2D and the health‐care professional was key to participation and that nudging captured through the design of the screening programme and the wording of the invitation letter was requested. Conclusion In preventive initiatives perceived as meaningful by the invitee, a focus on recruitment is crucial to facilitate participation. This study contributed with knowledge about how to promote participation by involving health‐care professionals in recruitment initiatives and through nudging. This knowledge may assist researchers, policymakers and ethicists' understanding and assessment of the ethical appropriateness and public acceptability of nudging in cardiovascular screening. Patient or public contribution By consulting 17 people with T2D, we are now in a position to suggest how a screening initiative should be altered because tools to improve uptake have been identified.